Comparative test of radiological exposure between femoral and radial techniques, development of a protective device and clinical trial design. Issue 3 (9th June 2015) - Bienert, Igor R C; Andrade, Pedro B; Rinaldi, Fabio S; Vilela, Fernanda D T; Silva, Paulo A; Braga, Joao C S; Waib, Paulo H; Rodrigues, Alexandre; Filho, Fábio V G; Okoshi, Katashi
Abstract : Background: Interventional procedures via radial technique have progressively increased due to improved patient comfort, lower complication rates and reduced mortality in some scenarios. One area of interest is radiation exposure and ways of minimising it. Most studies focus on patient radiation risk with conflicting results, but there is reasonable consensus for increased operator exposure from the radial technique. The aim of this study was to evaluate radiological exposure under controlled radial and femoral access simulation tests, mapping radiation paths and developing a radiological protection device for the transradial technique. Methods and results: Radiation exposure was simulated under controlled conditions for femoral and radial techniques using a pressurised ionisation chamber and water phantom. Different measurement points were defined according to standard positions to simulate radiation received by the operator in the gonads, thyroid and eyes at different angles during real procedures. The radial technique increased total exposure by 33% over the femoral technique. A protective device was developed and tested after radiation mapping. The protective device reduced cumulative radiation by 52% against the radial and 36% against the femoral technique. Conclusions: In our study, operator exposure to cumulative ionising radiation was higher from the radial technique and the protective device reduced radiation exposure levels in the radial and femoral techniques. These results provided the basis for a clinical trial design to better define the impact of the protection device and radiation exposure during real world practice using different interventional techniques. Trial registration number: http://www.clinicaltrials.gov . Unique identifier: NCT02200783 .